Risk of second primary cancer following myeloid neoplasia and risk of myeloid neoplasia as second primary cancer: a nationwide, observational follow up study in Sweden - Chattopadhyay, Subhayan; Zheng, Guoqiao; Sud, Amit; Yu, Hongyao; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli; Houlston, Richard; Hemminki, Kari (The lancet. Haematology, 2018)
Background - Although advances in the treatment of myeloid neoplasms have led to improved patient survival, this improvement has been accompanied by an increased risk of second primary cancer (ie, the risk of another cancer after myeloid neoplasia). We aimed to assess bi-directional associations between myeloid cancers and other cancers—ie, development of second primary cancer in patients who have previously had myeloid cancer, and risks of myeloid neoplasia in patients who have previously had another cancer—to provide insight into possible mechanisms beyond side-effects of treatment and shared risk factors. - Methods - Using the Swedish Family-Cancer Database, we identified 35 928 individuals with primary myeloid cancer, including myeloproliferative neoplasms, acute myeloid leukaemia, chronic myeloid leukaemia, and myelodysplastic syndrome diagnosed between 1958 and 2015. The Swedish Family-Cancer Database includes every individual registered as a resident in Sweden starting in 1932, with full parental history. The primary endpoint was the assessment of relative risks (RRs) for second primary cancer, which we performed using means of incidence rate ratios, regressed over a generalised Poisson model. - Findings - Between 1958 and 2015, overall relative risk of second primary cancers was significantly increased after acute myeloid leukaemia (RR 1·29, 95% CI 1·17-1·41), chronic myeloid leukaemia (1·52, 1·35-1·69), myelodysplastic syndrome (1·42, 1·26-1·59), and all myeloproliferative neoplasms (1·37, 1·30-1·43) relative to the incidence of these cancers as first primary cancer. With myeloid neoplasia as a second primary cancer, risks were significantly increased for acute myeloid leukaemia (1·57, 1·48-1·65), chronic myeloid leukaemia (1·26, 1·13-1·40), and myelodysplastic syndrome (1·54, 1·42-1·67) relative to the incidence of these myeloid neoplasms as first primary cancers. Relative risk of upper aerodigestive tract cancer, squamous cell skin cancer, and non-Hodgkin lymphoma as second primary cancers were increased after all four types of myeloid neoplasia relative to their incidence as first primary cancers. High risks of myelodysplastic syndrome and acute myeloid leukaemia as second primary cancers were found after haematological cancers (RRs between 5·08 and 10·04). - Interpretation - The relative risks of second primary cancer are important for the long-term management of patients with myeloid cancers. The bi-directional associations of myeloid cancers with many other cancers suggest a number of candidate mechanisms that might contribute to the development and aetiology of a second primary cancer. These mechanisms might include immune dysfunction or the effects of treatment, and these should be assessed in future investigations. - Funding - Deutsche Krebshilfe, Jane and Aatos Erkko Foundation, Sigrid Juselius Foundation, Finnish Cancer Organizations, Swedish Research Council, ALF from Region Skåne, and Bloodwise.